Neutral winds from mesosphere to thermosphere—past, present, and future outlook - Dhadly, Manbharat; Sassi, Fabrizio; Emmert, John; Drob, Douglas; Conde, Mark; Wu, Qian; Makela, Jonathan; Budzien, Scott; Nicholas, Andy (Frontiers in Astronomy and Space Sciences, 2023)
The Earth's upper atmosphere (85-550 km) is the nearest region of geospace and is highly dynamic in nature. Neutral winds control a large portion of the dynamics in this region. They play a critical role in determining the state of the ionosphere-thermosphere (I-T) system at almost all latitudes and altitudes. Their influences range from wave breaking/dissipation in the MLT to global redistribution of energy and momentum deposited at high latitudes by the magnetosphere. Despite their known importance, global geospace neutral winds have remained one of the least sampled state parameters of the Earth’s upper atmosphere and are still poorly characterized even after multiple decades of observations. This paper presents an overview of historical neutral wind measurements and the critical need for their global height-resolved measurements. Some satellite missions are still operational and deliver valuable information on the contribution of neutral winds in global atmospheric dynamics. However, many significant gaps remain in their global monitoring, and our current understanding of the drivers of neutral winds is incomplete. We discuss the challenges posed by these measurement gaps in understanding geospace physics and weather. Further, we propose some wind observation solutions, including the simultaneous operations of upcoming NASA DYNAMIC and GDC missions as well as support for the development of ground-based observing methodologies, that will lead to fundamental advances in geospace science and address humanity's emerging space needs.